2004
DOI: 10.1038/sj.bjp.0705641
|View full text |Cite
|
Sign up to set email alerts
|

The contractile action of leukotriene B4 in the guinea‐pig lung involves a vascular component

Abstract: 1 Leukotriene B 4 (LTB 4 ) is a potent leukocyte chemoattractant, acting on specific receptors, BLT receptors. The aim of this study was to examine the mechanism of action of LTB 4 in the guinea-pig lung, using strips of lung parenchyma (GPLP), spirals of trachea (GPT) and bronchus (GPB) and rings of pulmonary artery (GPPA). Mechanical responses were studied in organ baths, and mediator release was assessed using enzyme immuno assay. 2 LTB 4 induced similar contractions of GPLP and GPPA, whereas LTB 4 had only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 33 publications
1
28
1
Order By: Relevance
“…4, 19, 20, and 30), was observed in human coronary artery SMC because a second addition of LTB 4 did not significantly increase whole-cell currents. The latter notion is supported further by the spontaneous reversibility of the LTB 4 -and U75302-induced currents, which is similar to results of previous pharmacological studies of BLT 1 receptors in other preparations (19,20). In sensory neurons, LTB 4 has been implicated in direct activation of ligandgated cation channels (31).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…4, 19, 20, and 30), was observed in human coronary artery SMC because a second addition of LTB 4 did not significantly increase whole-cell currents. The latter notion is supported further by the spontaneous reversibility of the LTB 4 -and U75302-induced currents, which is similar to results of previous pharmacological studies of BLT 1 receptors in other preparations (19,20). In sensory neurons, LTB 4 has been implicated in direct activation of ligandgated cation channels (31).…”
Section: Discussionsupporting
confidence: 85%
“…The migration of human coronary SMC toward LTB 4 was inhibited by the BLT receptor antagonists ONO 4057 and U75302. The latter compound selectively binds to BLT 1 receptors (5) and has been reported (19) to inhibit LTB 4 -induced BLT 1 receptor activation at the concentration used. At higher concentrations, U75302 is a partial agonist at the BLT 1 receptor, as shown by its stimulation of whole-cell currents and SMC proliferation in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LTB 4 is produced predominantly by activated neutrophils, but also by alveolar macrophages and in transcellular reactions involving inflammatory cells and surrounding structural elements [4]. In addition to recruiting neutrophils and causing increased microvascular permeability [5], LTB 4 may stimulate lymphocyte migration in the lung [6] and constriction of pulmonary blood vessels via indirect mechanisms [7]. In comparison with healthy subjects, the LTB 4 levels have been reported to be elevated in EBC collected from subjects with asthma [8], cystic fibrosis [9] and chronic obstructive pulmonary disease (COPD) [10].…”
mentioning
confidence: 99%
“…However, receptor functions of leukotrienes in the urethra are not precisely known at this moment. It has been reported that LTB 4 , known as a potent leukocyte chemoattractant, produced contractions in the guinea-pig trachea, bronchus, and pulmonary artery and in the human pulmonary artery (25). Taken together, Ephedra herb may contract the urethra by producing several metabolites of arachidonic acid besides by stimulating α 1 -adrenoceptors.…”
Section: +mentioning
confidence: 94%